The impact of environmental heterogeneity and life stage on the hindgut microbiota of Holotrichia parallela larvae (Coleoptera: Scarabaeidae). - Shengwei Huang; Hongyu Zhang (PLoS ONE, 2013)
Gut microbiota has diverse ecological and evolutionary effects on its hosts. However, the ways in which it responds to environmental heterogeneity and host physiology remain poorly understood. To this end, we surveyed intestinal microbiota of Holotrichia parallela larvae at different instars and from different geographic regions. Bacterial 16S rRNA gene clone libraries were constructed and clones were subsequently screened by DGGE and sequenced. Firmicutes and Proteobacteria were the major phyla, and bacteria belonging to Ruminococcaceae, Lachnospiraceae, Enterobacteriaceae, Desulfovibrionaceae and Rhodocyclaceae families were commonly found in all natural populations. However, bacterial diversity (Chao1 and Shannon indices) and community structure varied across host populations, and the observed variation can be explained by soil pH, organic carbon and total nitrogen, and the climate factors (e.g., mean annual temperature) of the locations where the populations were sampled. Furthermore, increases in the species richness and diversity of gut microbiota were observed during larval growth. Bacteroidetes comprised the dominant group in the first instar; however, Firmicutes composed the majority of the hindgut microbiota during the second and third instars. Our results suggest that the gut's bacterial community changes in response to environmental heterogeneity and host's physiology, possibly to meet the host's ecological needs or physiological demands.